HLA-DR and tuberculin tests in rheumatoid arthritis and tuberculosis. Issue 1 (January 1989) - Bahr, G M; Sattar, M A; Stanford, J L; Shaaban, M A; Al Shimali, B; Siddiqui, Z; Gabriel, M; Al Saffar, M; Shahin, A; Chugh, T D
Abstract : Responses to four new tuberculins were found to be significantly reduced in 46 patients with rheumatoid arthritis in comparison with a control group of 79. Except for tuberculin itself, the same was found in 111 patients with tuberculosis. In common with patients with tuberculosis and leprosy, those with rheumatoid arthritis did not respond to common mycobacterial (group i) antigen. Three DR haplotypes were found to have significant effects on skin test responsiveness of the rheumatoid patients but had little or no effect on that of the patients with tuberculosis and none on that of the healthy control group. Rheumatoid patients with the HLA-DR4 haplotype had significantly greater responses to all four reagents than did non-DR4 patients, but their responses to leprosin A and scrofulin remained significantly lower than those of the control group. Possession of HLA-DR3 haplotype was associated with skin test positivity approaching normal, but the sizes of responses were reduced. Possession of DR7 was associated with an unexpected reduction in skin test positivity, especially in the case of tuberculin. These results support the hypothesis that mycobacteria, or autoantigens cross reactive with mycobacteria, may be involved in the aetiology of rheumatoid arthritis. The results also show that the regulation and specificity of responsiveness to mycobacterial antigens are different in patients with rheumatoid arthritis with different HLA-DR haplotypes.